Target definition for shipwreck hunting - Kirsner, Kim (Frontiers in Psychology, 2015)
The research described in the present article was implemented to define the locations of two World War II shipwrecks, the German raider Kormoran, and the Australian light cruiser HMAS Sydney. The paper describes the long and complex trail that led through inefficient oceanographic prediction to ambiguous historical prediction involving a single report and on to precise cognitive prediction based on nine reports from more than 70 survivors, a process that yielded a single target position or ‘mean’ just 2.7 NM (nautical miles) from the wreck of Kormoran. Prediction for the position of the wreck of Sydney opened with wishful thinking that she had somehow reached the coast more than 100 NM away when cognitive analysis of the survivor’s reports actually provided the basis for accurate prediction in a position near to the wreck of Kormoran. In the account provided below, the focus on cognitive procedures emerged from, first, a review of a sample of the shipwreck hunts, and, second, growing awareness of the extraordinarily rich database available for this search, and the extent to which it was open to cognitive analysis. This review touches on both the trans-disciplinary and the cognitive or intra-disciplinary issues that so challenged the political entities responsible for supervising of the search for the wrecks of Kormoran and Sydney. One of the theoretical questions that emerged from these debate concerns the model of expertise advanced by Collins (2013). The decomposability of alleged forms of expertise is revealed as a fundamental problem for research projects that might or might not benefit from trans-disciplinary research. Where expertise can be decomposed for operational purposes, the traditional dividing lines between experts and novices, and fools for that matter, are much harder to discern, and require advanced and scientifically informed review.